PELUANG DAN TANTANGAN DIGITALISASI PENDIDIKAN DALAM PENCAPAIAN SDGs 2030 - Wulansari, Sri; Putri, Filea Immanuela; Rahman, Ichsan Fauzi (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
The digitalization of education has become an increasingly relevant topic in efforts to achieve the 2030 Sustainable Development Goals (SDGs). This research aims to find out what the opportunities and challenges are for digitalizing education in achieving the 2030 SDGs. The method used in this research is the literature review method to detail key findings from various relevant sources. The results of the literature analysis show that the opportunity for digitalization of education lies in the potential to increase the accessibility, quality and relevance of education. AI-powered education has the potential to expand students' learning experiences and support sustainable development goals. The integration of AI in education provides a great opportunity to develop a more effective and relevant education system, and with the independent campus program, it makes optimal use of information technology so that it improves quality and can also have a positive impact. The gap in digital access is one of the challenges that needs to be overcome. To overcome this challenge, cooperation between the government, educational institutions and the general public is needed to ensure that the digitalization of education contributes positively to the achievement of the 2030 SDGs. It is hoped that the existence of the SDGs can overcome the problem of education which is still unequal and can improve its quality in order to make education in Indonesia more advanced. Keywords: Quality education, Digital literacy, SDGs 2030, Opportunities and challenges in achieving the SDGs 2030 goals.